Traditional New Orleans Jazz : Conversations with the Men Who Make the Music - Jacobsen, Thomas W., 1935- (Book collections on Project MUSE., 2011)
Nearly a century after its beginnings, traditional jazz remains the definitive music of New Orleans and an international hallmark of the city. The enduring sound and boundless energy of this American art form has produced a long list of jazz legends. From Lionel Ferbos -- the cityAEs oldest working jazz musician -- to Grammy winner Irvin Mayfield, the musical heritage of traditional jazz lives on through each playerAEs passion. In Traditional New Orleans Jazz, veteran jazz journalist Thomas Jacobsen discusses that legacy with Ferbos, Mayfield, and a whoAEs who of the present-day sceneAEs ôtrad j.